Motivos de Eliminación en Competencias de Enduro Internacional, Categoría Jinete Adulto, en Chile (2007-2014) - Muñoz-Alonzo, Lisandro (2016)
The aim of this study was to determine the frequency of reasons for elimination in international endurance competitions (IEC) of 80-90, 120 and 160 km in Chile in the period of 2007-2014. Records were obtained from the International Equestrian Federation database. Registered data included the distance and number of participating horses as well as those that successfully completed the race and those eliminated. In the latter case, data considered those that were retired, disqualified and failed to qualify. Also, average speed of winners for each distance was obtained. Ninety nine races were evaluated (42 in the range of 80-90 km, 41 in 120 km, and 16 in 160 km), with 919 participating horses, from whom 564 (61.4%) completed the competition. There were 3.2% disqualified horses 4.1% retired and 31.3% failed to qualify. Within the later, 25.4% failed to qualify due to lameness, 4% for metabolic reasons and 2% for other reasons. Association was found between race distance and percentage of failed to qualify for lameness (p<0.05), with a higher percentage in races of 120 and 160 km. Moreover, the average speed of winners was lower in races of longer distances (p<0.001). It is concluded that in Chile, with the exception of the disqualification percentage, the overall and detailed percentage for elimination in IEC of 80-160 km is low.